Faulkner's inheritance : Faulkner and Yoknapatawpha, 2005 - Urgo, Joseph R.; Abadie, Ann J. (University Press of Mississippi, 2007)
Essays by Susan V. Donaldson, Lael Gold, Adam Gussow, Martin Kreiswirth, Jay Parini, Noel Polk, Judith L. Sensibar, Jon Smith, and Priscilla Wald. William Faulkner once said that the writer "collects his material all his life from everything he reads, from everything he listens to, everything he sees, and he stores that away in sort of a filing cabinet ... in my case it's not anything near as neat as a filing case; it's more like a junk box." Faulkner tended to be quite casual about his influences. For example, he referred to the South as "not very important to me. I just happ.